Identification and characterization of a novel conserved 46 kD maltoporin of Aeromonas hydrophila as a versatile vaccine candidate in European eel (Anguilla anguilla). Issue 64 (May 2017) - Feng, Jianjun; Lin, Peng; Guo, Songlin; Jia, Yuanyuan; Wang, Yilei; Zadlock, Frank; Zhang, Ziping
Abstract: European eel ( Anguilla anguilla ) is a crucial economic fish that has been plagued by Aeromonas hydrophila infections for many years. Vaccines that are cross-protective against multiple serotypes could provide an effective control against A. hydrophila -mediated diseases. The outer membrane proteins (OMPs) are highly immunogenic and capable of eliciting protective immune responses. This study reports the identification of a novel 46 kD maltoporin that is a conserved protective antigen for different serotypes of A. hydrophila . First, this study purified OMPs from the strains of A. hydrophila B10, B11, B12, B15, B19, and B20. Western blot analysis revealed that the 46 kD maltoporin of B11 could be strongly reacted with all the specific European eel antisera against the above OMPs from different serotypes A. hydrophila . Cloning and sequencing of the maltoporin revealed that it contains an open reading frame (ORF) of 1281 nucleotides encoding 426 amino acids. Further sequence alignment analysis using the NCBI Conserved Domain Database (CDD) along with performing three-dimensional structure analysis showed that this protein belongs to maltoporin family. Three different study groups of European eels were intraperitoneal injected with one of the following conditions: phosphate-buffered saline (PBS group), formaline-killed-whole-cell (FKC) of A. hydrophila (FKC group) or with the recombinant maltoporin (OMP group) to analyze the immunogenicity of the recombinant maltoporin purified by nickel chelate affinity chromatography. On 14, 21, 28 and 42 days post-vaccination respectively, proliferation of the whole blood cells, titers of specific antibody, and lysozyme activities of experimental eels were detected. On 28d post-vaccination, eels from the three groups were challenged by intraperitoneal injection with five different live strains of A. hydrophila (B10, B11, B15, B19, and B20). The results showed that the proliferation of whole blood cells in the OMP group was significantly enhanced on 14d and the serum antibody titers of vaccinated European eels in FKC and OMP group were significantly increased on 28d and 42d. Lysozyme activities in serum were significantly up-regulated in FKC and OMP groups on 21d. The relative percent survival (RPS) of OMP group challenged by A. hydrophila B10, B11, and B20 was 75%, 62.5%, and 88%. This was higher than the corresponding RPS of FKC group with 50%, 37.5%, and 66%, respectively. The RPS was up to 100% in both OMP and FKC group when challenged by A. hydrophila B15 and B19. These results indicate that the 46 kD maltoporin is an effective potent vaccine candidate against different serotypes of A. hydrophila. Highlights: We identified a novel 46 kD maltoporin as a common antigenic epitopes among different serotypes A. hydrophila . European eels immunized with recombinant maltoporin induce effective cross-protection against multiple A. hydrophila serotypes.